Medicinal Plants in Australia, Volume 3 – Plants, Potions and Poisons - Cock, I.E. (Pharmacognosy Communications)
Traditional medicines have remained popular in many parts of the world and have in fact recently been regaining ground on allopathic medicine as they are perceived as being ‘natural’. Many volumes have been written on plant based medicinal systems internationally. Australian Aborigines have a long history of using medicinal plants to maintain their health and well being prior to the arrival of European settlers. Despite this long history of medicinal plant usage and the unique nature of Australian plants, there is a notable absence of books dealing with the medicinal plants of Australia at a level accessible to both interested lay persons, as well as experts in the fi elds of botany and herbal medicine.